2009
DOI: 10.1007/s00595-008-3855-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary stent placement for late complete occlusion after aortoiliac reconstructive surgery: Report of a case

Abstract: We report a case that was successfully treated by primary stent placement without thrombolysis or thrombectomy for graft thrombosis after aortoiliac reconstructive surgery. A 79-year-old man presented with a 2-month history of severe intermittent claudication of the right leg. He had undergone a surgical repair of abdominal aortic aneurysm with a bifurcated polyester graft 3 years before presentation. Digital subtraction angiography revealed total occlusion of the right limb of the graft. He underwent primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, in cases of chronic occlusion, other methods such as thrombolytic therapy or extra-anatomical bypass are often adopted 2 because thrombectomy of a hardened thrombus has an increased potential of failure. Bare stent coverage is another treatment option, 3 although this procedure might result in shower embolization of the remnant thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…However, in cases of chronic occlusion, other methods such as thrombolytic therapy or extra-anatomical bypass are often adopted 2 because thrombectomy of a hardened thrombus has an increased potential of failure. Bare stent coverage is another treatment option, 3 although this procedure might result in shower embolization of the remnant thrombus.…”
Section: Introductionmentioning
confidence: 99%
“…The technique of primary stenting for complete graft-limb occlusion after aortoiliac reconstructive sur- gery was recently described by Kondo et al [3], who managed to recanalize a chronically thrombosed graft-limb of a bifurcated graft used for surgical repair of an abdominal aortic aneurysm (AAA). Although predilation is not recommended, in order to avoid plaque shift or distal embolism, we performed predilation in the occluded limb by using the simultaneous contralateral support of a dilated balloon, as recently described, to avoid the aforementioned risks and also to better support either the predilation or the stenting of the limb [4].…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al reported a case of primary stent replacement for late complete occlusion after aortoiliac reconstructive surgery. 1 Furthermore, there are many reports showing successful outcomes for endovascular aneurysm repair (EVAR). Endovascular treatment is now available for both occlusive diseases and aneurysms.…”
Section: Introductionmentioning
confidence: 99%